Influence of carrier materials and coatings on retinal pigment epithelium cultivation and functions - Dörschmann, Philipp; Böser, Sebastian; Isik, David; Arndt, Christine; Roider, Johann; Selhuber-Unkel, Christine; Klettner, Alexa (Experimental eye research, 2022)
Properties of retinal pigment epithelium (RPE) are relevant for the development of cell culture models concerning an exact reproduction of the ocular cell biology. Here, we want to investigate how different carrier materials and coatings influence proliferation, differentiation and functions of RPE in regard to development of a three-dimensional cell culture model based on primary porcine RPE. Human RPE cell line ARPE-19 and primary porcine RPE were used. Cells were cultivated on plates which were coated with collagen I, collagen IV, laminin or fibronectin, respectively, and cell numbers were assessed after different time periods via trypan blue staining. Also, the ARPE-19 were cultivated on polydimethylsiloxane (PDMS), alginate, gelatin methacrylate (GelMA), poly-N-isopropylacrylamide (PNIPAM) and cells number were assessed. Primary RPE were cultured on PDMS material. Supernatants were collected and analyzed via ELISA for their vascular endothelial growth factor (VEGF) and transforming growth factor β (TGF-β) content. After day 14 cells were lysed and retinal pigment epithelium-specific 65 kDa protein (RPE65) and bestrophin-1 (BEST1) expression was investigated via Western blot. Cellular functions were tested on collagen I, collagen IV, laminin and fibronectin with and without PDMS. Scratch assay was performed to detect wound healing 24 and 48 h after scratch application. Immunolabeling was used to highlight tight junctions in concert with Hoechst staining and phalloidin to label cell nuclei and actin filaments, respectively. Phagocytosis of fluorescently labeled latex beads opsonized with photoreceptor outer segments (POS) was assessed via fluorescence microscopy. Transepithelial electrical resistance was measured for detection of cellular barrier. Gene expression of RDH11 (retinol dehydrogenase 11), BEST1 (bestrophin 1) and TGFB1 (transforming growth factor beta 1) was investigated via real-time PCR. Only PDMS carrier material was appropriate for primary RPE and ARPE-19 cell cultivation. Coating of PDMS with laminin led to increased proliferation. In primary RPE, VEGF secretion was increased if PDMS was coated with laminin or fibronectin compared to uncoated PDMS. No significant changes in phagocytic ability and generation of tight junctions were detected between different coatings, but RPE65 expression was reduced on fibronectin coated PDMS. Laminin coating decreased TGF-β and increased BEST1 protein expression. Also, RPE on collagen IV showed highest TEER on transwell plates. The genes RDH11 and TGFB1 were decreased when coated with collagen IV without PDMS as well as coated PDMS. Laminin and collagen IV coating led to an increased wound healing. Cultivation of RPE and ARPE-1 on PDMS is a possible alternative for cell culture models whereas alginate, GelMA and PNIPAM were not suitable. Coating with laminin increased the proliferation, wound healing and VEGF secretion of the cells. The results suggest that laminin coated PDMS as carrier material is suitable for the development of 3D culture model systems.
Gesehen am 30.06.2022